Editor's Choice – High Heritability of Liability to Abdominal Aortic Aneurysms: A Population Based Twin Study. Issue 1 (July 2016) - Joergensen, T.M.M.; Christensen, K.; Lindholt, J.S.; Larsen, L.A.; Green, A.; Houlind, K.
Abstract : Objective: First degree relatives of patients with abdominal aortic aneurysm (AAA) have an increased risk of developing AAA; however, despite intensive investigation, the specific genetic factors involved in the development of the disease are still largely unknown. In twin studies the influence of genetic and environmental factors can be assessed by comparing concordance rates between monozygotic (MZ) and dizygotic (DZ) twins. Higher phenotypic similarity between MZ than DZ twins indicates a genetic attribution to the etiology. The objective of this study was to investigate the heritability of AAA among Danish twins using concordance rates and heritability estimates. Methods: The Danish Twin Registry was used to identify all Danish twin pairs (born 1880–1971) where both twins were alive on January 1, 1977. AAA cases were then identified using the National Patient Registry and the Registry of Cause of Death. Probandwise concordance rates were calculated and heritability estimated using structural equation modeling. Results: The study identified 414 twins with AAA; 69.8% (289/414) were men and 30.2% (125/414) women. The probandwise concordance rate in MZ twins was 30% (95% CI 20.3–43.3%) compared with 12% (95% CI 7.0–20.1%) in DZ twins. In the heritability analysis 77% (95% CI 67–85%) of the total variance was explained by additive genetic components and 23% (95% CI 15–33%) was explained by non-shared environmental factors. Conclusions: The probandwise concordance rate was found to be 2.5 times higher in MZ compared with DZ twins. An overall heritability of 77% was determined.